2016
DOI: 10.1002/lary.26324
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of regional Medicare expenditures for otolaryngology physician services

Abstract: NA. Laryngoscope, 127:1312-1317, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…1-7 Patient demographics (race/ethnicity, 8 age, 9 sex 9,10 ) may affect costs of care, as can characteristics of provider and hospital separate from clinical volume. 11 A few authors have even examined whether and how cost should influence medical care decisions. 12…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1-7 Patient demographics (race/ethnicity, 8 age, 9 sex 9,10 ) may affect costs of care, as can characteristics of provider and hospital separate from clinical volume. 11 A few authors have even examined whether and how cost should influence medical care decisions. 12…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Patient demographics (race/ethnicity, 8 age, 9 sex 9,10 ) may affect costs of care, as can characteristics of provider and hospital separate from clinical volume. 11 A few authors have even examined whether and how cost should influence medical care decisions. 12 The persistent increase in health care cost is systemic, affecting all stakeholders, including patients, care providers, and payers.…”
mentioning
confidence: 99%
“…Joinpoint regression showed that the overall trends in fluticasone claims were mainly driven by Midwestern states and some Southern states (Figure 2; Supplemental Table 3). In a study by Smith et al 27 Medicare costs for otolaryngology physician services showed wide geographical variations, and these discrepancies were strongly associated with the availability of otolaryngologists. It is likely that the regional patterns in our study are also partially due to the varying availability of health services.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar vein, regional Medicare expenditures for otolaryngology services vary widely and are strongly correlated with provider and hospital factors rather than clinical volume or population factors. 21,22 As a result, we chose a different method to approximate regional demand.…”
Section: Discussionmentioning
confidence: 99%